Identifying trends and developing solutions for incurred sample reanalysis failure investigations in a bioanalytical CRO. (February 2011) - Meng, Min; Reuschel, Scott; Bennett, Patrick
In 2007, the US FDA recommended that pharmaceutical companies and CROs conduct incurred sample reanalysis (ISR) following the analysis of study samples using validated methods. Between January 2008 and Deccember 2009, over 250 separate analytes were tested for ISR in our laboratory (a bioanalytical CRO). Among these, nine analytes initially failed for ISR. While thorough investigations were conducted to identify the root cause of ISR failure for each study, these investigations were often painfully tedious and very costly, both financially and in terms of project timelines. In this paper, three representative studies are presented to showcase the detailed investigation processes, methodologies and final conclusions of the ISR investigations. Additionally, all nine ISR failures are analyzed to identify trends or common elements of the studies or methods that might help identify potential problems before they occur. Furthermore, suggestions and recommendations to minimize future ISR failures are provided.